Biodesulfurization of high sulfur fat coal with indigenous and exotic microorganisms. (1st October 2018) - Ye, Junpei; Zhang, Panyue; Zhang, Guangming; Wang, Siqi; Nabi, Mohammad; Zhang, Qian; Zhang, Haibo
Abstract: Coal is the most abundant fossil fuel in the world and its combustion accompanies with the emission of SOX, which is responsible for serious environmental problems. To reduce the emission of SOX is essential for clean fuel. In the present study, indigenous microorganisms acclimatized from fat coal itself and exotic microorganisms from sewage sludge were used for coal biodesulfurization. X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), and Raman spectral analysis were used to investigate the structural change of fat coal during the bioleaching. Results showed that kaolinite and quartz were the main minerals, and pyrite was the main inorganic sulfide in fat coal. After 36-day biodesulfurization, the total sulfur in fat coal decreased from 5.07% to 2.77% and 2.75%, and the pyritic removal was 77.68% and 87.88% with indigenous and exotic microorganisms, respectively. The exotic microorganisms were more effective to oxidize the pyrite than the indigenous microorganisms. But both microorganisms did not interact with the organic sulfur, which existed as CS bond in fat coal. FT-IR analyses showed the damage of kaolinite structure, indicating potential microbial effect on kaolinite, which has not been reported before. Raman spectral analysis was for the first time used to investigate the changes of coal macromolecular structure during the bioleaching. FT-IR and Raman spectra confirmed the changes of aromatic CH, OH bonds, which led to the increase of carbon crystallinity index. Graphical abstract: Highlights: Exotic microorganisms were more effective with a pyrite removal of 87.88%. Layered structure of kaolinite was damaged by exotic microorganisms. Different microorganisms caused differences in jarosite formation. Macromolecule depolymerization resulted in increase of carbon crystallinity index.